A defect in the yeast plasma membrane urea transporter Dur3p is complemented by CpNIP1, a Nod26-like protein from zucchini ( Cucurbita pepo L.), and by Arabidopsis thaliana δ-TIP or γ-TIP - Klebl, Franz; Wolf, Michael; Sauer, Norbert (FEBS letters, 2003)
Dur3 encodes the yeast plasma membrane urea transporter and Δdur3 mutants are unable to grow on media containing low concentrations of urea as sole nitrogen source. Complementation of the Δdur3 mutant line with expression libraries generated from whole Arabidopsis thaliana seedlings or from zucchini ( Cucurbita pepo L.) vascular tissue yielded numerous lines that had regained the capacity to grow on low urea as sole nitrogen source. Analysis of several of these yeast lines revealed that the Δdur3 mutation was complemented either by δ-TIP (TIP= t onoplast i ntrinsic p rotein) or γ-TIP from Arabidopsis or by CpNIP1, a new NOD26-like protein from zucchini. δ-TIP (At3g16240) and γ-TIP (At2g36830) had previously been characterized as proteins facilitating the transport of water across the tonoplast membrane, and Nod26-like proteins were characterized as glycerol transporters. So far, transport of urea has not been described for any of the proteins described in this paper. Further analyses support this function of TIPs and nodulin 26-like intrinsic proteins in urea transport.